Risk Adaptiveness and Need for Achievement Leads to Managerial Effectiveness (Global Journal of Management and Business Research, 2013)
Fast and frequent change in technology has put the present day managers under pressure. This pressure has impact on their personality dimensions and consequently on their capabilities to perform. So, one of the most critical issue of modern era is to study the impact of changing psychological dimensions on managerial effectiveness. This research was aimed to study effects of improved psychological traits like need for achievement and risk adaptiveness on managerial effectiveness. Statistical universe for this study was the managers having experience of more than three years from governmental and non-governmental organizations. Managerial Effectiveness, Need for achie-vement and Risk adaptiveness among managers were assessed by using the Index of Managerial Effectiveness test devised by Walter W. Hudson (1993) Achievement Motive Test (AMT) developed by Bhargava, V.P. (1994) and Risk Adaptiveness Test (RAT) developed by Rishipal & Jain, N (2012) respectively. A cross-sectional and longitudinal study was conducted by using the before and after with control group research design to compare the effectiveness of treatment group consisting of ineffective managers having lower tendency of need for achievement and risk adaptiveness and control group consisting of the effective managers having higher degree of need for achievement and risk adaptiveness.
Keywords: behaviour modification therapy; effective managers; ineffective managers; managerial effectiveness; need for achievement; observation and suggestion t